Genetic modulation of protein expression in rat brain - Li, Ling; Wu, Zhiping; Guarracino, Andrea; Villani, Flavia; Kong, Dehui; Mancieri, Ariana; Zhang, Aijun; Saba, Laura; Chen, Hao; Brozka, Hana; Vales, Karel; Senko, Anna N; et al. (iScience, 2025)
Genetic variations in protein expression are implicated in a broad spectrum of common diseases and complex traits but remain less explored compared to mRNA and classical phenotypes. This study systematically analyzed brain proteomes in a rat family using tandem mass tag (TMT)-based quantitative mass spectrometry. We quantified 8,119 proteins across two parental strains (SHR/Olalpcv and BN-Lx/Cub) and 29 HXB/BXH recombinant inbred (RI) strains, identifying 597 proteins with differential expression and 464 proteins linked to cis-acting quantitative trait loci (pQTLs). Proteogenomics identified 95 variant peptides, and sex-specific analyses revealed both shared and distinct cis-pQTLs. We improved the ability to pinpoint candidate genes underlying pQTLs by utilizing the rat pangenome and explored the connections between pQTLs in rats and human disorders. Collectively, this study highlights the value of large proteo-genetic datasets in elucidating protein modulation in the brain and its links to complex central nervous system (CNS) traits.
Keywords: Biochemistry; Genetics; Neuroscience